Evaluation of goods & services among white and black consumers - Cambitzi, Creon (My University, 1991)
The research investigated the evaluation of common goods and services by white and black consumers, and to determine where similarities and dissimilarities between these two segments existed. A review of the literature on consumer behaviour, with specific reference to decision making models, and a series of in depth interviews enabled the expansion of the Zeithaml (1981) set of constructs by a factor of two. A questionnaire was developed and administered to white and black employees of well known local firms in a variety of industries. Hypothesis testing enabled validation of the expanded set of constructs, and the comparison of white and black evaluative differences, while correspondence ;analysis determined the key evaluative dimensions. Important new dimensions discovered included Convenience, Loyalty and Reception. An invaluable method of clustering was found in the /chi squared trees technique. The results indicated that black consumers are significantly less experienced in the use and evaluation of common services compared to their white counterparts. As a result of this inexperience, a much less sophisticated set of key evaluative constructs are relied upon in the decision process. Both segments appear to be /ciware of generally higher risks associated with services, but are less prone to invest effort in information gathering prior to purchase. The white segment purchases services based on their convenience, whilst the black segment faces equal inconvenience for any purchase. The most significant marketing implications drawn were firstly, the need to appreciate consumer perceptual similarities across, and differences within, goods and services categories. Secondly, marketers need very different strategies for the black segment.
Thesis(M.B.A.)--University of the Witwatersrand, 1991
Keywords: Consumer behaviour--South Africa; Consumer goods; Service industries; Marketing; Service industries--Marketing